PENYUSUNAN SOP MANAJEMEN INSIDEN KEHILANGAN ATAU PENCURIAN DATA PADA DSDABM KOTA BANDUNG MENGGUNAKAN FRAMEWORK ITIL V3 - Muchamad Sobri Sungkar; Irvan Muhammad Akbar; Arrahman Mukhlis Harimadi (Power Elektronik : Jurnal Orang Elektro, 2022)
Abstract  With the development of Information Technology at the Bandung City DSDABM, it has an impact on the high user needs, both the use of devices, IT services and the need for data and information security. With the existence of vulnerabilities and threats to both IT equipment and data and information, there is a need for incident management in dealing with any IT problems or as a function of IT services to users so that business processes can continue to run. This study will describe the incident management process flow, incident category, service strategy and incident escalation flow based on the proposed ITIL V3 Framework. The result of this research is the preparation of incident management SOP documents that are clearer and more structured both to users and to IT managers in carrying out IT equipment maintenance, service and handling of each incident. Keywords: Information Technology, Security, Data and Information, Incident Management, ITIL V3